Motivations for alumni gifting to their alma mater in two South African universities - Nemakhavhani, Kesaobaka Dephney (University of the Witwatersrand, Johannesburg, 2024)
There is a growing expectation that South African universities should actively seek new income streams, one of these being alumni gifts. However, there is insufficient understanding of what motivates alumni to give to their alma mater. Guided by social identity theory, this study investigated the motivations for alumni gifting to contribute to the knowledge that could assist South African universities in developing evidence- based resource mobilisation strategies that incorporate alumni gifting. The study applied a quantitative research methodology – specifically a survey – in examining variables that motivate alumni gifting at two South African universities. Particularly, the study sought alumni views, opinions, attitudes and behaviours to test whether the social identity ethos of Ubuntu guides alumni gifting in two South African universities. The study found that while gender, social identity, convenience, and social responsibility in the form of active citizenship are important factors explaining the future intention to give, solicitation is the strongest predictor for alumni gifting to their alma mater in the two South African universities. Furthermore, the findings suggest that alumni, in their capacity as active citizens, exhibit a heightened sense of social responsibility which influences their gifting behaviour. The findings of this study are important for South African universities. Universities may consider implementing some recommendations to boost their fundraising appeals to their alumni. Based on the study results, the development and alumni practitioners could garner alumni support by strengthening their solicitation plan and implementing convenient systems and processes for alumni gifting. In addition, segmenting potential alumni donors by gender could help universities better target their solicitation efforts. Universities could further consider implementing social impact programmes that capacitate their students (pre-alumni) to be active citizens pre- and post-graduation. This suggests that alumni's past experience as students may impact their future intention to give. Future research can expand on this topic and other African gifting practices and behaviours
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of African Philanthropy to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Alumni gifting; Motivations; Ubuntu, Social identity; Alma mater; African Philanthropy; UCTD; SDG-4: Quality education